)The political role of Numan bin Bashir Al-Ansari at the beginning of the establishment of the Umayyad state( - Mohammed , Assistant Lecturer (lark, 2025)
Praise be to Allah, and peace and blessings be upon the most honorable of the prophets and messengers, Abu al-Qasim Muhammad and his family....        This research deals with an Islamic figure, which is Numan bin Bashir Al-Ansari, who was born in the year 2 AH and died in 64 AH, and the purpose of this research is to know the political role played by this character in the establishment of the Umayyad state, especially after the martyrdom of the Prophet Muhammad (peace and blessings of God be upon him) until his death and address some of the positions he held at the time of the Umayyad Caliphate in the era of Muawiyah, and some differences and strife occurred during his assumption of those positions in Iraq and in Levant as well as Hijaz.       The study of any Islamic figure is an important study in Islamic history, so the axes of this research have been divided into several axes and we will address the first section his name, lineage and surname, as well as his family and some other important things, the second section we will address some of the political positions that were for Numan bin Bashir Al-Ansari, and his position on the revolution of Muslim bin Aqeel, as well as we will mention some other positions and we will present them in historical texts and are discussed.                 The third section we will mention the political role that played Numan bin Bashir Ansari in the Umayyad era, when the succession ascended Muawiya bin Abi Sufyan and after him his son Yazid and after him Muawiya bin Yazid, and came after them Marwan bin judgment, and what happened from the political and religious turmoil during the rule of the Umayyads until the killing of Numan bin Bashir Ansari. The conclusion of the research, results and recommendations has become clear to us that Numan bin Bashir Ansari had a prominent political and leadership role in the Umayyad Caliphate where we find him granted Muawiyah several positions was Wali was a leader and again an adviser because he was one of the men of Bani Umayyah and loyal to them, but we find Numan in the latest events has joined the front of Abdullah bin Zubayr when he declared himself Khalifa, and he has fought and defended the sons of Zubair in all the events that happened and that we will address in our research God willing.
Keywords: The role- political- Al-Nu'man bin Bashir- beginning- establishment- Umayyad state.